Pulse oximeter perfusion index as a new predictor of hypotension following subarachnoid block in lower segment Cesarean section: A prospective randomized study - Ashish Mohan M; Suman Gupta; Kavya Kanjikkal; Vankudoth Bhaskar (Asian Journal of Medical Sciences, 2025)
Background: Hypotension is a common adverse effect of spinal anesthesia, especially during pregnancy, due to the blockade of pre-ganglionic sympathetic fibers, resulting in reduced peripheral vascular resistance. This study explores the perfusion index (PI) as a potential predictor for hypotension during spinal anesthesia in lower segment Cesarean sections (LSCS). Aims and Objectives: The aim of the study was to study the correlation between baseline PI and the incidence of hypotension following subarachnoid block in LSCS. Materials and Methods: This prospective observational study included 90 parturients, divided into two groups based on baseline PI: Group 1 (PI≤3.5) and Group 2 (PI>3.5). Spinal anesthesia was administered with 10 mg of 0.5% hyperbaric bupivacaine at the L3-L4 interspace. The study evaluated the correlation between baseline PI and the degree of hypotension, as well as PI’s predictive capacity for hypotension during Cesarean delivery. Results: Hypotension occurred in 35.55% of Group 1 and 75.55% of Group 2 (P<0.001). A significant correlation was found between baseline PI>3.5 and both the incidence of hypotension and the total mephentermine dose required (P<0.001). The sensitivity and specificity of PI>3.5 for predicting hypotension were 68% and 72.5%, respectively. The area under the receiver operating characteristic curve for PI as a predictor of hypotension was 0.914. Conclusion: A higher baseline PI is associated with a higher incidence and severity of hypotension following spinal anesthesia. Baseline PI is a reliable predictor of spinal anesthesia-induced hypotension during Cesarean delivery and could be used for early identification and management of at-risk patients.